Rationale for and Review of Neoadjuvant Therapy Prior to Radical Prostatectomy for Patients with High-Risk Prostate Cancer - McKay, Rana R. (2013)
Despite state of the art local therapy a significant portion of men with high-risk prostate cancer develop progressive disease. Neoadjuvant systemic therapy prior to radical prostatectomy (RP) is an approach which can potentially maximize survival outcomes in patients with localized disease. This approach is under investigation with a wide array of agents and provides an opportunity to assess pathologic and biologic activity of novel treatments. The aim of this review is to explore the past and present role of neoadjuvant therapy prior to definitive therapy with RP in patients with high-risk localized or locally advanced disease. The results of neoadjuvant ADT, including use of newer agents such as abiraterone and enzalutamide, are promising. Neoadjuvant chemotherapy, primarily with docetaxel, with or without ADT has also demonstrated efficacy in men with high-risk disease. Other novel agents targeting the vascular endothelial growth factor receptor (VEGFR), epidermal growth factor receptor (EGFR), platelet derived growth factor receptor (PDGFR), clusterin, and the immune system are currently under investigation and have led to variable results in early clinical trials. Despite optimistic data, approval of neoadjuvant therapy prior to RP in patients with high-risk prostate cancer will depend on positive results from well designed phase III trials.